(untitled) (Materiali di Estetica. Terza serie, 2022)
This paper analyses the work Riflessioni sulla violenza written by Georges Sorel and published in 1908. The principal aim of this paper is to present the deep relationship between myth, violence and politics in order to reevaluate how irrational forces have guided social movements and revolutions. The distinction between the notions of force and violence introduces the central thesis of Georges Sorel’s political thought, which is called anarcho-syndacalism. More specifically, George Sorel puts together Marx and Bergson in order to develop a severe criticism of the Third Republic and to theorize the role of violence in the transition from capitalism to socialism. Through the myth of the general strike, Sorel introduces his philosophical perspective on social struggles against the parlamentarism.